Synthesis of 4,6-dimethyl-3-cyano-2-pyridone catalysed by amino acids - Nevena Ž. Prlainović; Nataša Ž. Šekuljica; Jelena M. Mirković; Dušan Ž. Mijin (Zaštita Materijala)
In this work the synthesis of 4,6-dimethyl-3-cyano-2-pyridone catalyzed by amino acids was studied. In the first part of the work, the optimization was carried out by varying the initial concentration of glycine, the molar ratio of the reactants (acetylacetone and cyanoacetamide) and the reaction time. It has been found that it is necessary to heat the reaction mixture and that the optimum concentration of the amino acid is 0.2 mmol cm-3. It was also found that the optimal concentration of cyanoacetamide is 3.0 mmol cm-3 (molar ratio cyanoacetamide: acetyl acetone = 3:1), and that the reaction time is 24 h. In the second part of the work, the influence of the structure of 19amino acids on the yield of 4,6- dimethyl-3-cyano-2-pyridone was investigated, using the optimal reaction conditions. It was found that the highest yield was achieved with arginine (almost 90%) and than with histidine (about 85%). With the most of other amino acid the yield was 50-60%.